Leasing operacyjny jako najkorzystniejszy sposób zakupu nowego samochodu osobowego przez mikroprzedsiębiorcę - Kozłowski, Jarosław (Leasing - The Best Way to Buy a New Car by a Small Businessman, 2008)
Nowadays in the stabilized legal and economic situation operational leasing has become the most advantageous way of using a passenger car. It owes its attractiveness mainly to the effect of expenses on its repayment in the tax sphere. Each amount spent that way on the purchase of a car becomes the cost incurred to general income. There is no limit of expenses to the equivalent of 20 000 euros, which take place while financing the purchase of a car with a bank loan or with one's own funds. Financing a purchase with operational leasing enables, after the repayment, the sale of a car without having to pay a sales tax.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 350-356